ANALISA KAPASITAS PARKING STAND TERHADAP PELAYANAN PESAWAT UDARA SAAT PEAK HOURS DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Dedi Yusuf Trenggono; Anton Budiarto; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Zainuddin Abdul Madjid Lombok Airport has 24 parking stands that are ready to be used to serve the need for aircraft parking spaces. The number of flights is always increasing every year and to prepare for the biggest motorbike race in the world, MotoGP, then this research was conducted which aims to calculate the capacity and needs of the parking stand to serve aircraft during peak hours, and to anticipate an aircraft surge that is predicted to occur during the MotoGP events. The research is using data that contains the number of flights per hour. By using the queue theory calculation method, it can be seen the utilization of the parking stand in crowded or quiet conditions. The results showed that the parking stand was crowded during peak hours, and besides peak hours, the use of parking stand does not reach 50% of the capacity. The results from calculation of the use of parking stand during peak hours and during the MotoGP event show that the parking stand is almost entirely used and the utilization rate reaches 62,5%, so the optimization must be done in order to anticipate unwanted accidents.